Diseño de auditoría para los procesos de la empresa colprinter ltda asociados a seguridad alimentaria y calidad (2014)
The company COLPRINTER LTDA is a medium-sized organization that is dedicated to the production of different advertising products. Throughout their career they have created different production lines aimed at the preparation of food packaging such as chocolates, hamburgers, donuts, among others. Among the objectives of the management is to expand its service nationwide, ensuring recognition in the market to acquire new customers. According to this, senior management is interested in seeking new management strategies aimed at the continuous improvement of their processes, and by the same request of some customers to include the issue of food safety in their packaging. At present, the Organization has documented a quality manual, which has allowed it to approach management initiatives in this area, but they have very little information and guidelines on the food safety part. According to this, there is a need to review what has already been established in the Organization in relation to management systems through an audit, in order to obtain the maximum benefit from the actual information and generate initiatives. of improvement to meet the requirements of customers and objectives of COLPRINTER LTDA.